Tuberculosis patients face high treatment support costs in Colombia, 2021. - Oscar Andrés Cruz Martínez; Ingrid García; Gloria Mercedes Puerto; Nelson J Alvis-Zakzuk; Martha Patricia López; Juan Carlos Moreno Cubides; Ángela María Sánchez Salazar; Julián Trujillo Trujillo; Claudia Marcela Castro-Osorio; Vivian Vanessa Rubio; Carlos Castañeda-Orjuela; Ernesto Montoro; et al. (PLoS ONE)
Objective To estimate the baseline to measure one of the three indicators of the World Health Organization (WHO) End TB strategy (2015-2035), measure the costs incurred by patients affected by tuberculosis (TB) during a treatment episode and estimate the proportion of households facing catastrophic costs (CC) and associated risk factors, in Colombia, 2021. Material and methods A nationally representative cross-sectional survey was conducted among participants on TB treatment in Colombia, using telephone interviews due to the exceptional context of the COVID-19 pandemic. The survey collected household costs (direct [medical and non-medical out-of-pocket expenses] and indirect) over an episode of TB, loss of time, coping measures, self-reported income, and asset ownership. Total costs were expressed as a proportion of annual household income and analyzed for risk factors of CC (defined as costs above 20% annual household income). Results The proportion of TB-affected households incurring in costs above 20% annual household income (CC) was 51.7% (95%CI: 45.4-58.0) overall, 51.3% (95%CI: 44.9-57.7) among patients with drug-sensitive (DS) TB, and 65.0% (95%CI: 48.0-82.0) among drug-resistant (DR). The average patient cost of a TB case in Colombia was $1,218 (95%CI 1,106-1,330) including $860.9 (95%CI 776.1-945.7) for non-medical costs, $339 (95%CI 257-421) for the indirect costs, and $18.1 (95%CI 11.9-24.4) for the medical costs. The factors that influenced the probability of facing CC were income quintile, job loss, DR-TB patient, and TB type. Conclusion Main cost drivers for CC were non-medical out-of-pocket expenses and income loss (indirect costs). Current social protection programs ought to be expanded to mitigate the proportion of TB-affected households facing CC in Colombia, especially those with lower income levels.